RNA Virus Population Diversity, an Optimum for Maximal Fitness and Virulence - Korboukh, Victoria K.; Lee, Cheri A.; Acevedo, Ashley; Vignuzzi, Marco; Xiao, Yinghong; Arnold, Jamie J.; Hemperly, Stephen; Graci, Jason D.; August, Avery; Andino, Raul; Cameron, Craig E. (The Journal of biological chemistry, 2014)
The ability of an RNA virus to exist as a population of genetically distinct variants permits the virus to overcome events during infections that would otherwise limit virus multiplication or drive the population to extinction. Viral genetic diversity is created by the ribonucleotide misincorporation frequency of the viral RNA-dependent RNA polymerase (RdRp). We have identified a poliovirus (PV) RdRp derivative (H273R) possessing a mutator phenotype. GMP misincorporation efficiency for H273R RdRp in vitro was increased by 2–3-fold that manifested in a 2–3-fold increase in the diversity of the H273R PV population in cells. Circular sequencing analysis indicated that some mutations were RdRp-independent. Consistent with the population genetics theory, H273R PV was driven to extinction more easily than WT in cell culture. Furthermore, we observed a substantial reduction in H273R PV virulence, measured as the ability to cause paralysis in the cPVR mouse model. Reduced virulence correlated with the inability of H273R PV to sustain replication in tissues/organs in which WT persists. Despite the attenuated phenotype, H273R PV was capable of replicating in mice to levels sufficient to induce a protective immune response, even when the infecting dose used was insufficient to elicit any visual signs of infection. We conclude that optimal RdRp fidelity is a virulence determinant that can be targeted for viral attenuation or antiviral therapies, and we suggest that the RdRp may not be the only source of mutations in a RNA virus genome.